2013
DOI: 10.4103/0301-4738.107191
|View full text |Cite
|
Sign up to set email alerts
|

The British Asian Community Eye Study: Outline of results on the prevalence of eye disease in British Asians with origins from the Indian subcontinent

Abstract: Background:Asians from the Indian Subcontinent form the largest ethnic minority in the United Kingdom. Data on the prevalence of visually-impairing eye conditions in this population are vital for planning eye health care services.Materials and Methods:This survey was based in the two London boroughs with the largest Asian populations. Subjects originating from the Indian Subcontinent were identified from GP practice records. All subjects were asked about demographic details and were given a full ophthalmologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 25 publications
(35 reference statements)
1
3
0
Order By: Relevance
“…The dominant sense organ condition for all ethnic groups was cataracts. This pattern is consistent with a UK survey of South Asian patients that showed higher cataract prevalence than the general population of the UK and the US [ 31 ].…”
Section: Discussionsupporting
confidence: 91%
“…The dominant sense organ condition for all ethnic groups was cataracts. This pattern is consistent with a UK survey of South Asian patients that showed higher cataract prevalence than the general population of the UK and the US [ 31 ].…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, the pattern of disease has been described differently in Asian populations as compared to European populations, potentially due to anterior chamber and angle anatomy [8]. In comparison, studies done on POAG have been conducted in a wide variety of Asian populations, finding prevalence rates ranging from as low as 1.0% to as high as 6.5% (Table 1) [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Additionally, studies have estimated that approximately 70% of all POAG cases in Asians were of the normal-tension variety [13,24].…”
Section: Incidence and Prevalencementioning
confidence: 99%
“…These racial differences in risk and potential mechanistic pathways necessitate an improved understanding of glaucoma pathology to more effectively treat individuals of Asian descent. To date, the most important data available on the epidemiology of primary forms of glaucoma (including POAG with high IOP, NTG, and PACG) in Asians are from a diverse set of studies [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]; however, findings have not been well synthesized to properly evaluate the specifics of the disease within the Asian population as well as its ethnic subgroups; therefore, in this review, we will summarize the current literature on primary forms of glaucoma with an emphasis on understanding NTG and its impact in aging Asian populations.…”
Section: Introductionmentioning
confidence: 99%
“…[15,16] and certain eye conditions which can lead to V.I. [17][18][19]. A UK survey of 2077 adults aged 18 and over showed that, when self-rating the quality of their vision, people from MEC were around twice as likely to rate their vision as Poor/Very Poor in comparison to those who were White British (14% vs. 7%, respectively) [20].…”
Section: Introductionmentioning
confidence: 99%